The acute abdomen in the older person. Issue 1 (February 2013) - McCarthy, K; Hardy, K; Ackermann, C; Hewitt, J
The acute abdomen is a common condition in older people. Half of all presentations to hospital require admission, with a third requiring immediate surgery. The Royal College of Surgeons of England have reported a worryingly high mortality rate in the over 80s undergoing emergency surgery, with a 3-fold difference in mortality throughout the England, Wales and Northern Ireland. The aim of this article is to highlight the issues that older people face in relation to acute abdominal pathology.